Non-steroidal Anti-inflammatory Drugs in Tonic, Phasic and Inflammatory Mouse Models - Miranda, Hugo F.; Noriega, Viviana; Sierralta, Fernando; Poblete, Paula; Aranda, Nicolas; Prieto, Juan Carlos (Drug Research, 2019)
The principal mechanism of action of non-steroidal anti-inflammatory drugs (NSAIDs) is the inhibition of ciclooxigenases. In this study was evaluated if NSAIDs could induce antinociceptive differences according to the type of murine pain model. Male mice were injected intraperitoneally with meloxicam, diclofenac, piroxicam, metamizol, ibuprofen, naproxen and paracetamol in the writhing, tail flick and formalin orofacial tests and dose-response were analyzed to obtain the ED50 of each drugs. Administration of NSAIDs produced in a dose-dependent antinociception with different potency in the tests. The relative potency of NSAIDs among the tests shows a value of 5.53 in the orofacial formalin test in phase I and 6.34 in phase II between meloxicam and paracetamol; of 7.60 in the writhing test between meloxicam and paracetamol and of 8.46 in the tail flick test between ibuprofen and paracetamol. If the comparison is made for each NSAID in the different tests, the minimum value was 0.01 for between writhing and phase II of the orofacial formalin. Meanwhile, the highest power ratio was 11.71 for diclofenac between writhing and tail flick tests. In conclusion, the results suggests that intraperitoneal NSAIDs administration induce antinociceptive activity depending on the type of pain. The results support that NSAIDs administration, induce a wide variety of antinociceptive effect, depending on the type of pain. This suggest the participation of different mechanisms of action that can be added to the simple inhibition of COXs controlled by NSAIDs.
Keywords: non-steroidal anti-inflammatory drugs; writhing test; tail flick assay; formalin orofacial test